Protective effect of Lactobacillus casei HY2782 against particulate matter toxicity in human intestinal CCD-18Co cells and Caenorhabditis elegans - Kim, Joo Yeon; Lee, So Young; Jung, Seung-Hee; Kim, Mi Ri; Choi, Il-Dong; Lee, Jung-Lyoul; Sim, Jae-Hun; Pan, Cheol-Ho; Kang, Kyungsu (SPRINGER, 2020)
Objectives To investigate the preventive effect of Lactobacillus casei HY2782 on toxicity induced by particulate matter (PM, inhalable particles less than 10 mu m in diameter) in human intestinal CCD-18Co cells and a model animal Caenorhabditis elegans. Results L. casei HY2782 treatment prevented PM-induced intestinal cell death via cellular reactive oxygen species production and membrane disruption attenuation. PM significantly decreased the total number of eggs laid and the body bending activity of C. elegans, demonstrating PM toxicity. L. casei HY2782 treatment restored the reproductive toxicity and decline in locomotion activity induced by PM in C. elegans. Overall, L. casei HY2782 attenuated PM toxicity in vitro in cultured intestinal cells and in vivo in the model nematode. Conclusion Our study provides a potential clue for developing L. casei HY2782 probiotics that attenuate PM-induced cellular and physiological toxicity; however, further in-depth preclinical trials using mammalian animal models and clinical trials are required.
Keywords: TOPOISOMERASE INHIBITOR; PM2.5; PROBIOTICS; HEALTH; MODEL